Preparação, caracterização e degradação de nanobiocompósitos poliméricos envolvendo polilactídeos e nanocristais de celulose - Everton Luiz de Paula (2013)
In this study, nanobiocomposites were prepared from polylactide ( PLAs ) and cellulose nanocrystals ( NCCs ) to determine the effect of these nanoparticles on barrier and reinforcing properties and degradation rate of these polymeric matrices. The NCCs are known to be cellulose crystalline domains. The NCCs are noted for their biodegradabilityand their excellent mechanical, optical and thermal properties. However, that can incorporate these properties to hydrophobic matrices, such materials should be sufficiently dispersed, which is possible through the chemical modification of its surface or by formation of covalent bonds between the polymer matrix and the NCCs . For the preparation of NCCs was used the acid hydrolysis of eucalyptus pulp with H2SO4. As a first alternative modification of the NCCs was used Fischer esterification withthree different organic acids: ethanoic, hexanoic and neopentanoic acids. Then, the modified and unmodified NCCs were characterized using various techniques, which include: contact angle, IV-FT , elemental analysis , TEM and XRD . The results showed that the NCCs obtained showed an average length of 145 ± 25 nm and an aspect ratio(length / width ) of 24. The surface modification was confirmed by the appearance characteristic bands of infrared ester groups and an increase in the percentage of carbon in the nanocrystals modified by elemental analysis. The preparation of bionanocomposites of PLAs with NCCs was conducted using four different strategies. For the first two, was used PDLLA, an amorphous polymer while the last two PLLA, a semi crystalline polymer. First, the NCCs unmodified were dispersed in PDLLA. Characterized by spectroscopic , thermal and mechanical analysis showed a good interfacial adhesion and an increase of the mechanical properties of the matrix. In a second strategy was usedpolyethylene glycol (PEG) as a dispersant of the nanocrystals, in order to improve adhesion to the polymer matrix of the NCCs . The results obtained by DSC showed that the addition of PEG leads to a decrease in thermal stability of the matrix also acts as a plasticizer, significantly reducing the Tg of PDLLA. However, the effect of the nanocrystals is limited since the influence of PEG is much more pronounced for being ingreater quantities. In the third strategy NCCs modified with neopentanoic acid were incorporated into PLLA. It was verified by SEM and DSC that NCCs act as nucleating agents of the matrix leading to the formation of new crystalline domains. A good interaction between the fillers and PLLA was confirmed by improved thermal and mechanical properties causing, for example, to an increase of the initial temperature of degradation, and a 100% increase in tensile strength . The fourth and final strategy for incorporating the NCCs consisted of method called grafting from. In this methodology the lactide monomer could be polymerized from thesurface of the NCCs rich in hydroxyl groups. It was used a magnesium based as catalyst, to replace the conventional tin-based catalyst, used for the synthesis of polylactides. Infrared spectroscopic analysis, 1H NMR and XPS showed the efficiency of polymerization at the surface of the nanocrystals. For the nanocomposites prepared in this way was observed a significant improvement in the storage modulus of the composites, as compared with pure PLLA matrix and the composites obtained with the NCCs without chemical modification . Themechanical rigidity was interpreted as being the result of several factors, such as a higher degree of crystallinity, better dispersion of the filler in the matrix and strong interfacial adhesion between the nanoparticles with the polymer. Finally, the composites were subjected to two tests of degradation in the first, called hydrolytic degradation, the samples were subjected to a phosphate buffer solution medium, (pH = 7.4 and temperature of 37 °C), simulating the bodily fluids aiming at biomedicalapplications. In the second experiment the samples were subjected to degradation in composted soil as a means microbial active. In both tests, the objective was to evaluate the influence of the nanocrystals in the degradation of the matrix. For the of results hydrolytic degradation the tests revealed that the NCCs strongly influence the kinetics of thehydrolytic degradation, decreasing considerably the degradation rate. For the composted soil, the results showed that the NCCs to accelerate the degradation of the matrices since they are primarily degraded by microbial action.